Menuju Kemajuan Ekonomi: Rancang Bangun Sentra Kuliner sebagai Strategi Peningkatan Pertumbuhan Ekonomi di Kabupaten Sragen - Isa, Muzakar; Praswati, Aflit Nuryulia; Sina, Helmia Khalifah; Wahyudi, Agus; Suwondo, Agus; Kurniawan, Wawan (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
This study aims to analyze regional leading sectors and regional leading products in order to increase economic growth, as well as formulate a strategy for developing the Brigadier General Veteran Katamso culinary center, Sragen Regency. This research uses an explanatory method using primary and secondary data, and uses 3 analytical tools, namely Shift share analysis, Location Quotient analysis and SWOT analysis. The results of the research show that Sragen Regency has six leading sectors, namely the Agriculture, Forestry and Fishing sector, the mining and quarrying sector, the Manufacturing sector, the Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles sector, the Accommodation and Food Service Activities sector, and the education sector. In this leading sector, Sragen Regency has 16 leading products, namely furniture, batik, household appliances, convection, patchwork crafts, processed food, woven bags, goyor sarongs, bamboo crafts, bird cages, stone crafts, organic rice, bricks , herbal medicine, performing arts, red tilapia, catfish and catfish, and honey. The Culinary Center is part of the development of the food service activities sector. This sector is a regional leading sector which has sectoral growth and large distribution of the GRDP of Sragen Regency. The Brigadier General Katamso Veteran Culinary Center is in a strategic location, and has complete facilities and infrastructure so it has the potential to become a profitable culinary center. In structuring and maintaining the sustainability of culinary centers, it is recommended to provide quality products at competitive prices, organize locations and provide supporting facilities, partnerships to organize related events at these locations, digital marketing that is attractive and distributed regularly and regularly, and strengthens traders' institutions in selling.